CLINICAL AND LABORATORY FEATURES OF VACCINATION AGAINST COVID-19 IN PREGNANT WOMEN - Mamajonova , Diyorakhon; Shukurov , Farkhad (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
Objective: to evaluate the safety, efficacy, and immunogenicity of COVID-19 vaccination in pregnant women. Materials and research methods. The study included 120 pregnant women vaccinated with the Gam-Kovid-Vak vaccine against COVID-19. Of these, 60 women were vaccinated in the second trimester of pregnancy (main group I) and 60 in the third trimester of pregnancy (main group II), and the comparison group consisted of 30 pregnant women who refused vaccination. The study used clinical, immunological, hormonal, ultrasound, Doppler and statistical research methods. Results and its discussion. Analysis of post-vaccination reactogenicity in women vaccinated against COVID-19 showed the manifestation of very weak local and general reactions, the formation of immunogenicity up to 87%, the analysis of the hormonal status and the fetoplacental system did not reveal pronounced pathological abnormalities. Conclusion: Vaccination of pregnant women against COVID-19 leads to a high level of immunity in pregnant women, i.e. 87%, leads to a 2.5-fold decrease in the incidence of coronavirus infection in mothers, 1.7 times in newborns, and also leads to a 1.8% decrease in complications associated with COVID-19 during pregnancy.